Does extreme maternal age still act as a risk factor for adverse perinatal outcome? Evidence from Poland 20 years after the social and economic transformation - Kosińska, Magdalena; Hadada, Tomasz; Liczbińska, Grażyna (Anthropological Review, 2019)
It was examined whether positive changes in maternal SES and medical facilities in Poland 20 years after social and economic transformation weakened the role of maternal age in shaping perinatal outcome. Data comprised of 2,979 children born in 2000 and 2,992 – born in 2015. To test the differences between the frequency of indicators of adverse perinatal outcome the chi-square test was applied. The influence of maternal age on the perinatal outcome was estimated using Generalized Linear Models (GLMs), with binomial error distribution and the logit link function. The infants survival was examined using survival analysis. Gestational age and birth weight were influenced by mother’s age and the year of survey. Infants of adolescent and older mothers represented the groups with a risk of adverse perinatal outcome: an increase of preterm births and higher risk of having children with LBW in the group of adolescent mothers than in mothers aged >35, infants born SGA and LGA found in both adolescent and adult mothers. GLMs confirmed the impact of maternal age and the year of survey on perinatal outcome. The Cox proportional hazard models showed that the year of survey was the only factor affecting the risk of infants’ death. The impact of maternal age on adverse perinatal outcome can be counterbalanced by positive changes in social and economic standard of living of women, improvement in neonatal medical care and better equipment of hospital wards in 2015 as compared to 2000.